Welfare Reform and Social Investment Policy International Lessons and Policy Implications. - Jun Choi, Young (Research in comparative & global social policy., 2021)
Providing original observations, this seminal text analyses the emergence of social investment policies in both Europe and East Asia. Experts explore the roads and barriers towards effective social investment policies, derive practical social policy implications and highlight important lessons for future social policymaking.